Kronik Viral Hepatit B ve C’de Serum Leptin Düzeyinin Önemi. The Importance of Serum Leptin Level in Chronic Viral Hepatitis B and C - Şenol, Arzu; Toraman, Zülal Aşcı (Uşak Cerrahi Derneği, 2021)
Objective: Leptin plays an important role in inflammation and liver fibrogenesis in viral liver diseases. In this study, determination of serum leptin level and the effect of leptin levels on liver inflammation and fibrosis in chronic hepatitis B (CHB) and chronic hepatitis C (CHC) cases were evaluated. Materials and Methods: The study groups consisted of 75 CHB, 36 CHC patients and 51 healthy subjects were included in the study as the control group. Liver biopsy specimens were scored using Ishak histological scoring system. Serum leptin levels were determined by ELISA method. Results: 39 of the chronic hepatitis B cases were female, 36 were male, 18 of the CHC cases were female, 18 were male, and 26 of the control group were female 25 one was male. Serum leptin levels were statistically significantly higher in CHB and CHC cases than in the control group (p: 0.001). However, there was no statistically significant difference in serum leptin level between CHC and CHB cases. There was no statistically significant difference between serum leptin levels and age, gender, and biochemical parameters (P> 0.05). Serum leptin levels were statistically significantly higher in patients with significant fibrosis in chronic hepatitis B and KHC patients compared to those with mild fibrosis. Conclusion: Leptin plays a role in liver inflammation and fibrosis in CHB and CHC. Leptin level indicates advanced fibrosis. In CHB and CHC patients, leptin levels can be used to evaluate the degree of advanced fibrosis and in clinical follow-up, but larger studies are needed.

OBJECTIVE: Leptin plays an important role in inflammation and liver fibrogenesis in viral liver diseases. In this study, determination of serum leptin level and the effect of leptin levels on liver inflammation and fibrosis in chronic hepatitis B (CHB) and chronic hepatitis C (CHC) cases were evaluated.MATERIALS AND METHODS: In this prospective clinical research study, a total of 75 CHB patients, 36 CHC patients, and a 51 control group were included. Liver biopsy specimens were scored using Ishak histological scoring system. Serum leptin levels were determined by ELISA method.RESULTS: Overall, 39 of CHB cases were female while 36 was male, there were 18 female and 18 male cases of CHC, while the control group consisted of 26 female and 25 male. Serum leptin levels were statistically significantly higher in CHB (2.81±0.38) and CHC (2.97±0.35) cases than in the control group (1.39±0.08) (p: 0.001). However, there was no statistically significant difference in serum leptin level between CHC and CHB cases. There was no statistically significant difference between serum leptin levels and age, gender, and biochemical parameters (P> 0.05). Serum leptin levels were statistically significantly higher in patients with significant fibrosis in chronic hepatitis B and KHC patients compared to those with mild fibrosis (P<0.05).CONCLUSION: Leptin plays a role in liver inflammation and fibrosis in CHB and CHC. In CHB and CHC patients, leptin levels can be used to evaluate the degree of advanced fibrosis and in clinical follow-up, but larger studies are needed.
The Importance of Serum Leptin Level in Chronic Viral Hepatitis B and C
Keywords: Clinical Sciences; Klinik Tıp Bilimleri